যদি \(a=\cfrac{√5+1}{√5-1}\) ও \(b=\cfrac{√5-1}{√5+1}\) হয়, তবে \(\cfrac{a^2+ab+b^2}{a^2-ab+b^2}\) এর মান নির্ণয় করি ।


\(a+b= \cfrac{√5+1}{√5-1}+\cfrac{√5-1}{√5+1}\)
\(= \cfrac{(√5+1)^2+(√5-1)^2}{(√5-1)(√5+1)}\)
\(= \cfrac{2(5+1)}{5-1}\)
\(= \cfrac{12}{4}=3\)

\(ab=\cfrac{√5+1}{√5-1}\times \cfrac{√5-1}{√5+1}=1\)

\(\cfrac{a^2+ab+b^2}{a^2-ab+b^2} \)
\(=\cfrac{(a+b)^2-2ab+ab}{(a+b)^2-2ab-ab} \)
\(=\cfrac{(a+b)^2-ab}{(a+b)^2-3ab} \)
\(=\cfrac{(3)^2-1}{(3)^2-3} \)
\(=\cfrac{9-1}{9-3} \)
\(=\cfrac{8}{6}=\cfrac{4}{3} \)

Similar Questions